EMPOWERMENT OF THE BENEFICIARY FAMILY (KPM) OF THE HOPE FAMILY PROGRAM (PKH) THROUGH THE SOCIAL ENTREPRENEURSHIP PROGRAM (PROKUS) IN CILEBAR DISTRICT, KARAWANG REGENCY - Umi Hani (Jurnal Multidisiplin Sahombu, 2023)
Prokus is a program launched by the Ministry of Social Affairs of the Republic of Indonesia which targets beneficiary families (KPM) who have graduated or left the Family Hope Program (PKH) so that independence is formed. economically so that they do not go back down economically after they no longer receive assistance through PKH. Graduation KPM-PKH themselves are those who are still in the poor and vulnerable category but are graduated because some of the components do not fulfill them. As stated by the Director General of Social Empowerment of the Indonesian Ministry of Social Affairs, "ProKUS simply empowers the community through a business approach. The purpose of this study was to find out how the process of empowering KPM PKH through Prokus in Cilebar District, Karawang Regency was viewed from the empowerment of PKH KPM in implementing social entrepreneurship programs accompanied by District Social Welfare Workers (TKSK) as social assistants. This study uses a descriptive method, with a qualitative approach. Data collection techniques used are observation, interviews, and documentation. Data analysis was carried out by means of data reduction, data clarification, data verification, and drawing conclusions. Based on the six aspects above, KPM ProKUS is grouped into beginner categories, developing categories and advanced categories. In the Cilebar District KPM there are two categories, namely the beginner category of 14 KPM and the developing category of 3 KPM. This program is expected to break the dependence of KPM on social assistance and create and enhance the spirit of social entrepreneurship and business independence. The outputs and achievement targets of this research are in the form of accepted scientific articles in accredited national journals. Research Technology Readiness Level target in year 1 is scale 2.